Vitamin A nutritional status in high‐ and low‐income postpartum women and its effect on colostrum and the requirements of the term newborn - Cristiane Santos Sânzio Gurgel; Evellyn C. Grilo; Larissa Q. Lira; Débora G.F. Assunção; Priscila G. Oliveira; Larisse R.M. de Melo; Silvia V. de Medeiros; Luanna C. Pessanha; Roberto Dimenstein; Clélia O. Lyra (Brazilian Society of Pediatrics, 2018)
Objective: To evaluate the vitamin A status in serum and colostrum of postpartum women with different socioeconomic status, comparing the colostrum retinol supply with the vitamin A requirement of the newborn. Methods: Cross-sectional study conducted with 424 postpartum women. Vitamin A maternal dietary intake was estimated using a food frequency questionnaire. Colostrum and serum retinol levels were measured by high performance liquid chromatography (HPLC). Serum retinol concentrations <20 μg/dL were indicative of vitamin A deficiency (VAD). Vitamin A levels provided by colostrum <400 μgRAE/day were considered as insufficient for term newborns. Results: The mean maternal vitamin A intake during pregnancy was 872.2 ± 639.2 μgRAE/day in low-income women and 1169.2 ± 695.2 μgRAE/day for high-income women (p < 0.005). The prevalence of vitamin A deficiency was 6.9% (n = 18) in the low-income group and 3.7% (n = 6) in the high-income group. The estimated mean retinol intake by infants of the high- and low-income mothers were 343.3 μgRAE/day (85.8% AI) and 427.2 μgRAE/day (106.8% AI), respectively. Conclusions: Serum vitamin A deficiency was considered a mild public health problem in both populations; however, newborns of low‐income women were more likely to receive lower retinol levels through colostrum when compared with newborns of high‐income mothers.